Penerapan Peraturan Menteri Kesehatan Republik Indonesia Nomor 12 Tahun 2017 Dalam Pemberian Vaksin - Dwi Erwinta Wicaksono; Anggraeni Endah Kusumaningrum (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
The purpose of this study is to examine and analyze the application of the law within the Ministry of State of the Republic of Indonesia Health Regulation Number 12 of 2017 concerning the Implementation of Immunization and the reasons why parents do not give immunizations to their children. The research approach uses empirical juridical. The results of this study are 1) The application of the law in the Ministry of State of the Republic of Indonesia Health Regulation Number 12 of 2017 concerning the Implementation of Immunization has not been effective. Factors that prevent parents from carrying out their obligations, namely parents who do not give vaccines to their children due to religious factors. The refusal occurred because there were those who thought that the vaccine was not halal, parents did not want their children to be vaccinated but wanted their children to grow up healthy naturally or with herbal medicine in an emergency (as seen from the parent's certificate of refusal to give the vaccine).